2021
DOI: 10.3390/coatings11121566
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Structures and Properties of Detonation Coatings with α-Al2O3 and γ-Al2O3 Main Phases

Abstract: This study is aimed at obtaining a coating of aluminum oxide containing α-Al2O3 as the main phase by detonation spraying, as well as a comparative study of the structural, tribological and mechanical properties of coatings with the main phases of α-Al2O3 and γ-Al2O3. It was experimentally revealed for the first time that the use of propane as a combustible gas and the optimization of the technological regime of detonation spraying leads to the formation of an aluminum oxide coating containing α-Al2O3 as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Consequently, the structural and phase characteristics of aluminum oxide coatings are significantly affected by the technological parameters of detonation spraying. Our previous studies [23][24][25] also confirmed that changes in parameters such as the explosion frequency and the volume filled with the gas mixture in the barrel lead to changes in the content of α-Al 2 O 3 and γ-Al 2 O 3 phases in the coatings. In our studies [23][24][25], we used α-Al 2 O 3 as a starting powder and investigated the effects of maximum parameters on a CCDS2000 detonation machine.…”
Section: Introductionsupporting
confidence: 58%
“…Consequently, the structural and phase characteristics of aluminum oxide coatings are significantly affected by the technological parameters of detonation spraying. Our previous studies [23][24][25] also confirmed that changes in parameters such as the explosion frequency and the volume filled with the gas mixture in the barrel lead to changes in the content of α-Al 2 O 3 and γ-Al 2 O 3 phases in the coatings. In our studies [23][24][25], we used α-Al 2 O 3 as a starting powder and investigated the effects of maximum parameters on a CCDS2000 detonation machine.…”
Section: Introductionsupporting
confidence: 58%
“…Composite HATi coatings with a thickness of about 60 μm were applied to a Ti6Al4V substrate using a CCDS2000 detonation complex (CCDS-2000, developed by Siberian Protective Coating Technologies LLC, Novosibirsk, Russia), the operation principle of which is described in detail in [20,21]. Detonation spraying is performed by feeding combustible and oxidizing gases (propane, oxygen) into the channel in a ratio close to stoichiometric.…”
Section: Methodsmentioning
confidence: 99%
“…Obviously, the nature of detonation spraying-interaction with gaseous products of an exothermic chemical reaction-is close to flame spraying. However, in contrast to it, there is no strong heating of the part, which is related to the pulse character of the detonation spraying process [12].…”
Section: Introductionmentioning
confidence: 99%